Differential binding efficiency between the envelope protein of Japanese encephalitis virus variants and heparan sulfate on the cell surface - Liu, Hsiuan; Chiou, Shyan-Song; Chen, Wei-June (Journal of medical virology, 2004)
Japanese encephalitis (JE) virus infects a number of host cells, either mosquitoes or vertebrates, in nature. The viral envelope (E) protein is known to interact with molecule(s) on the cell membrane during the early stage of virus infection. In this study, two sets of virus variants including T1P1‐L4/T1P1‐S1 and CJN‐L1/CJN‐S1 derived from two strains (T1P1 and CJN) of the JE virus were used to evaluate the effects of genomic variations on virus entry. Each set of virus variant (T1P1‐L4/T1P1‐S1 or CJN‐L1/CJN‐S1) possessed a single amino acid variation in the E protein. The variation of Glu/Lys at E‐306 was found between T1P1‐L4 and T1P1‐S1 whereas the same variation at E‐138 was seen between CJN‐L1 and CJN‐S1. The results showed that heparan sulfate (HS) differentially expressed on the surface of different types of host cells was essential for JE virus infection as shown in an evident difference in attachment efficiency between CHO‐K1 cells and its mutant with defects in GAG biosynthesis. Furthermore, differential interaction of heparin with the envelope protein of JE virus variants implies the significance of virus mutations (especially Lys for E‐138 and/or E306 in this case) that are rather likely involved in determining efficiencies of viral attachment, penetration, and eventual infection. J. Med. Virol. 72:618–624, 2004. © 2004 Wiley‐Liss, Inc.